2021
DOI: 10.1002/jum.15935
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Agreement and Correlation of an Automated Algorithm for B‐Line Identification and Quantification With Expert Sonologist Review in a Handheld Ultrasound Device

Abstract: Objectives-B-lines are ultrasound artifacts that can be used to detect a variety of pathologic lung conditions. Computer-aided methods to detect and quantify B-lines may standardize quantification and improve diagnosis by novice users. We sought to test the performance of an automated algorithm for the detection and quantification of B-lines in a handheld ultrasound device (HHUD).Methods-Ultrasound images were prospectively collected on adult emergency department patients with dyspnea. Images from the first 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Recently various algorithms were built for the measurement of B lines in in vivo (32), intensive care unit (12), emergency department ( 9) and patients with dyspnoea (13). The ICC ranged from 0.79-0.94, similar to our ndings (0.892, whereas > 0.75 was considered good performance) (9,10). Unlike our analysis, none of these studies translated into the diagnostic evaluation of uid status or correlated to other objective uid assessments (e.g.…”
Section: Automated Lus B-line Detection In Dialysis Patientssupporting
confidence: 75%
See 1 more Smart Citation
“…Recently various algorithms were built for the measurement of B lines in in vivo (32), intensive care unit (12), emergency department ( 9) and patients with dyspnoea (13). The ICC ranged from 0.79-0.94, similar to our ndings (0.892, whereas > 0.75 was considered good performance) (9,10). Unlike our analysis, none of these studies translated into the diagnostic evaluation of uid status or correlated to other objective uid assessments (e.g.…”
Section: Automated Lus B-line Detection In Dialysis Patientssupporting
confidence: 75%
“…However, a study using HHUSD versus a high-end ultrasound system (HEUS) to assess B-line count in heart failure patients showed fewer B-lines on HHUSD due to the limited clip store capacity of 2-seconds in HHUSD compared to at least 6 seconds in HEUS (8). We target to standardise the identi cations of B lines; regardless of the level of experience of the staff, the measurement method or the complexity of the device, automated detection by arti cial intelligence (AI) is demonstrated to be feasible and reliable (9,10). Automated B-line detection can be processed by algorithms from deep learning methods (11) and dedicated segmentation, which was shown to be moderately correlated with extracellular lung water (12).…”
Section: Introductionmentioning
confidence: 99%
“…Spatial and temporal resolution and deep learning algorithms have demonstrated variable effects in early studies, having the potential for greater or lesser sensitivity, and are likely bounded by the subjective image search and acquisition process. [45][46][47] Nonetheless, this study has demonstrated that a specific ultrasound examination can be performed during telehealth by patients without any prior training and has future implications for this methodology in other disease states. In COVID-19, the simplified lung examination could be performed not only from home isolation by patients but also in emergency departments, urgent care facilities, or COVID-19 testing centers for outpatients with minimal symptoms.…”
Section: Discussionmentioning
confidence: 84%
“…We also observed similar diagnostic power between physician and AI counts of B lines. Recently various algorithms were built for the measurement of B lines in in vivo [ 34 ], intensive care unit [ 14 ], emergency department [ 11 ] and patients with dyspnoea [ 15 ]. The ICC ranged from 0.79–0.94, similar to our findings (0.892, whereas > 0.75 was considered good performance) [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a study using HHUSD versus a high-end ultrasound system (HEUS) to assess B-line count in heart failure patients did show fewer B-lines on HHUSD due to the limited clip store capacity of 2-seconds in HHUSD compared to at least 6 seconds in HEUS [ 10 ]. We target to standardise the identifications of B lines; regardless of the level of experience of the staff, the measurement method or the complexity of the device, automated detection by artificial intelligence (AI) is demonstrated to be feasible and reliable [ 11 , 12 ]. Automated B-line detection can be processed by algorithms from deep learning methods [ 13 ] and dedicated segmentation, which was shown to be moderately correlated with extracellular lung water [ 14 ].…”
Section: Introductionmentioning
confidence: 99%